How do you solve \[{{\left( \ln x \right)}^{2}}=\ln \left( {{x}^{2}} \right)\]?
Answer
Verified
442.2k+ views
Hint:In the given question we have been asked to find the value of ‘x’ and it is given that \[{{\left( \ln x \right)}^{2}}=\ln \left( {{x}^{2}} \right)\]. In order to solve the question, first we need to use the basic property of logarithms i.e. \[\ln \left( {{a}^{b}} \right)=b\ln \left( x \right)\] and \[{{\log }_{b}}\left( x \right)=y\] is equivalent to\[{{b}^{y}}=x\]. Then we simplify the equation further to get the possible values of ‘x’.
Formula used:
\[\ln \left( {{a}^{b}} \right)=b\ln \left( x \right)\]
If \[x\] and b are positive real numbers and b is not equal to 1,
Then \[{{\log }_{b}}\left( x \right)=y\] is equivalent to \[{{b}^{y}}=x\].
Complete step by step solution:
We have given that,
\[{{\left( \ln x \right)}^{2}}=\ln \left( {{x}^{2}} \right)\]
As, we know that,
\[\ln \left( {{a}^{b}} \right)=b\ln \left( x \right)\]
Applying this in the given equation, we get
\[\Rightarrow {{\left( \ln x \right)}^{2}}=2\ln \left( x \right)\]
Substitute ln (x) = k,
Now, solving the equation, we get
\[\Rightarrow {{k}^{2}}=2k\]
Write the above equation in the standard form, we get
\[\Rightarrow {{k}^{2}}-2k=0\]
Taking out ‘k’ as a common factor, we get
\[\Rightarrow k\times \left( k-2 \right)=0\]
Solving each term individually, we get
\[\Rightarrow k=0\] And \[k-2=0\]
\[\Rightarrow k=0\] And \[k=2\]
Now, undo the substitution i.e. k = ln (x), we get
\[\Rightarrow \ln \left( x \right)=0\] and \[\ln \left( x \right)=2\]
Now, solving
\[\Rightarrow \ln \left( x \right)=0\]
Using the definition of log,
If \[x\] and b are positive real numbers and b is not equal to 1,
Then \[{{\log }_{b}}\left( x \right)=y\]is equivalent to\[{{b}^{y}}=x\].
\[\Rightarrow {{e}^{0}}=x\]
\[\Rightarrow x=1\]
Similarly, solving
\[\Rightarrow \ln \left( x \right)=2\]
\[\Rightarrow {{e}^{2}}=x\]
\[\Rightarrow x={{e}^{2}}\]
Therefore, the possible values of ‘x’ are 1 and \[{{e}^{2}}\].
It is the required solution.
Note: In the given question, we need to find the value of ‘x’. To solve these types of questions, we used the basic formulas of logarithm. Students should always require to keep in mind all the formulae for solving the question easily. After applying log formulae to the equation, we need to solve the equation in the way we solve general linear equations.
Formula used:
\[\ln \left( {{a}^{b}} \right)=b\ln \left( x \right)\]
If \[x\] and b are positive real numbers and b is not equal to 1,
Then \[{{\log }_{b}}\left( x \right)=y\] is equivalent to \[{{b}^{y}}=x\].
Complete step by step solution:
We have given that,
\[{{\left( \ln x \right)}^{2}}=\ln \left( {{x}^{2}} \right)\]
As, we know that,
\[\ln \left( {{a}^{b}} \right)=b\ln \left( x \right)\]
Applying this in the given equation, we get
\[\Rightarrow {{\left( \ln x \right)}^{2}}=2\ln \left( x \right)\]
Substitute ln (x) = k,
Now, solving the equation, we get
\[\Rightarrow {{k}^{2}}=2k\]
Write the above equation in the standard form, we get
\[\Rightarrow {{k}^{2}}-2k=0\]
Taking out ‘k’ as a common factor, we get
\[\Rightarrow k\times \left( k-2 \right)=0\]
Solving each term individually, we get
\[\Rightarrow k=0\] And \[k-2=0\]
\[\Rightarrow k=0\] And \[k=2\]
Now, undo the substitution i.e. k = ln (x), we get
\[\Rightarrow \ln \left( x \right)=0\] and \[\ln \left( x \right)=2\]
Now, solving
\[\Rightarrow \ln \left( x \right)=0\]
Using the definition of log,
If \[x\] and b are positive real numbers and b is not equal to 1,
Then \[{{\log }_{b}}\left( x \right)=y\]is equivalent to\[{{b}^{y}}=x\].
\[\Rightarrow {{e}^{0}}=x\]
\[\Rightarrow x=1\]
Similarly, solving
\[\Rightarrow \ln \left( x \right)=2\]
\[\Rightarrow {{e}^{2}}=x\]
\[\Rightarrow x={{e}^{2}}\]
Therefore, the possible values of ‘x’ are 1 and \[{{e}^{2}}\].
It is the required solution.
Note: In the given question, we need to find the value of ‘x’. To solve these types of questions, we used the basic formulas of logarithm. Students should always require to keep in mind all the formulae for solving the question easily. After applying log formulae to the equation, we need to solve the equation in the way we solve general linear equations.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE